2021
DOI: 10.1002/stem.3371
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Quality Control and Identification of Human Keratinocyte Stem Cells by Deep Learning-Based Automated Cell Tracking

Abstract: Stem cell-based products have clinical and industrial applications. Thus, there is a need to develop quality control methods to standardize stem cell manufacturing. Here, we report a deep learning-based automated cell tracking (DeepACT) technology for noninvasive quality control and identification of cultured human stem cells. The combination of deep learning-based cascading cell detection and Kalman filter algorithm-based tracking successfully tracked the individual cells within the densely packed human epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The alteration of keratinocyte stem cell dynamics is assumed to be involved in the age-dependent decline of skin regenerative capacity, but the underlying mechanism is unknown. Cell locomotion in human keratinocyte colonies was first reported >40 yr ago by Sun and Green (1976) , and recent studies have revealed that cell motility is associated with the proliferative capacity of human epidermal and oral keratinocytes ( Hirose et al, 2021 ; Hoshikawa et al, 2021 ; Hoshikawa et al, 2019 ; Kinoshita et al, 2019 ; Nanba et al, 2015 ; Tate et al, 2015 ). Here we demonstrated that an age-dependent decline of EGFR signaling impairs keratinocyte stem cell motility and reepithelialization through COL17A1 proteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…The alteration of keratinocyte stem cell dynamics is assumed to be involved in the age-dependent decline of skin regenerative capacity, but the underlying mechanism is unknown. Cell locomotion in human keratinocyte colonies was first reported >40 yr ago by Sun and Green (1976) , and recent studies have revealed that cell motility is associated with the proliferative capacity of human epidermal and oral keratinocytes ( Hirose et al, 2021 ; Hoshikawa et al, 2021 ; Hoshikawa et al, 2019 ; Kinoshita et al, 2019 ; Nanba et al, 2015 ; Tate et al, 2015 ). Here we demonstrated that an age-dependent decline of EGFR signaling impairs keratinocyte stem cell motility and reepithelialization through COL17A1 proteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…The observation of human epidermal stem cells was complicated because of the impossibility of applying DNA labels or genetic modifications. The primary knowledge was obtained from keratinocyte culture: epidermal cells produced the different clones in vitro; stem cells formed large, self-renewing holoclones; whereas TA cells produced abortive clones because they divided a small number of times and underwent terminal differentiation [ 91 , 92 ]. Combining the xenografting approach with viral transfection visualized the epidermal clones directly in the human epidermis [ 93 ].…”
Section: Actual Questions From Mouse To Human Skinmentioning
confidence: 99%
“…AI technologies have been applied in cell biology for the automation of intricate biological image recognition, which is only possible for skilled trainees with expertise. For example, in recent studies using microscope cell images, an AI model distinguished keratinocyte SC colonies from non-SC colonies [ 9 ]. AI accurately classified the state of cultured iPS cells into colonies, single cells, differentiated cells, and dead cells, as performed by a trainee with iPS cell culture expertise [ 10 ].…”
Section: Introductionmentioning
confidence: 99%